The Role of Civil Law in Resolving Unfair Dismissal Disputes: An Empirical Study in Indonesian Labor Courts - Muhlizar, Muhlizar; Purba, Nelvitia; Warman, Syafil (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the application of civil law principles in resolving unfair dismissal disputes within Indonesian labor courts through a mixed-methods empirical analysis. The research investigates how Indonesian civil law frameworks, particularly those grounded in the Civil Code (Kitab Undang-Undang Hukum Perdata), interact with labor-specific legislation in addressing employment termination disputes . Using a qualitative-quantitative approach, this study analyzes 150 labor court decisions from 2020-2024 and conducts in-depth interviews with 30 legal practitioners, judges, and labor law experts . The findings reveal that civil law principles, especially those relating to contract validity under Article 1320 of the Indonesian Civil Code, play a crucial role in determining the fairness of dismissal procedures . The study identifies significant gaps in the application of civil law remedies, with only 35% of unfair dismissal cases receiving adequate compensation through civil law mechanisms . The research demonstrates that while Indonesian labor courts increasingly rely on civil law principles for dispute resolution, inconsistencies in judicial interpretation and enforcement mechanisms limit their effectiveness . This study contributes to the understanding of how civil law can be better integrated into labor dispute resolution frameworks to enhance worker protection and ensure equitable outcomes in employment termination cases.